(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2011)
Introduction: Pre-operative fasting period is poorly monitored in developing countries though it may lead to critical consequences especially in the parturient women and their neonates. Objective: In this prospective randomized study, conducted over a period of six months, influences of pre-operative fasting time on maternal and neonatal blood glucose level in elective caesarean section under sub-arachnoid block was observed. Methods: Three equally sized (n=20) groups with different pre-operative fasting period (Group A: 4 hours, Group B: 6 hours and Group C: 7.9±1.15 hours) were taken into consideration. Maternal blood glucose level was measured on day before operation (as baseline), on day of surgery before starting infusion and just after baby delivery. Neonatal umbilical cord blood glucose just after delivery was also measured by strip method. Results: Baseline blood glucose level of group C mother was 5.41±0.43 mmol/L, whereas glucose level before starting infusion and just after deliver was 4.46±0.45 mmol/L and 4.60±0.39 mmol/L respectively. In group A and group B, these changes were not significant (p>0.05). There was marked reduction in maternal blood glucose level in group C (p<0.001). Neonatal blood glucose level was reduced in all three groups as compared to placental circulation concept (70-80% of placental flow). No mother or neonate showed critical hypoglycaemia (in mother <4.0 mmol/L and in neonate <2.5 mmol/L). Highly significant inverse correlation was observed between maternal fasting time and blood glucose before starting infusion (r= 0.706, p <0.001), and maternal blood glucose and neonatal cord blood glucose level (r= -0.937, p <0.001). Conclusion: Though, no significant correlation could be detected between maternal fasting time and neonatal blood glucose level (r= -0.196, p >0.05) neonatal blood glucose level was reduced in group C. Key words: Pre-operative fasting time; caesarean section; sub-arachnoid block; neonatal cord blood glucose DOI: 10.3329/jafmc.v6i2.7269 JAFMC Bangladesh. Vol 6, No 2 (December) 2010 pp.21-24